Natural serine proteases and their applications in combating amyloid formation - Sanjay Metkar; Saranya Udayakumar; Agnishwar Girigoswami; Koyeli Girigoswami (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Amyloidosis is a group of diseases including diabetes type II and neurological disorders, such as Alzheimer's disease, Parkinson's disease, prion disease, etc., where a common trait is observed; accumulation of misfolded protein at different parts of the body, especially the brain which manifests the typical symptoms like dementia, movement disorders, etc. These misfolded proteins, named amyloids, are protease resistant and thus it becomes difficult to manage these diseases in vivo. Enzymes that catalyse the complete breakdown of proteins are known as proteases. The peptide bonds in proteins are degraded by these serine proteases, which cause amyloid disaggregation. Experimental approach: We have searched for related articles using the search engines Google Scholar, PubMed, and Scopus for the past 10 years, selected the relevant articles, and written the outcomes and benefits of protease using the medical topic "serine protease" and the following text phrases -keratinase, lumbrokinase, serratiopeptidase, nattokinase. Key results: Alkaline serine proteases exhibit activity within the neutral to alkaline pH range. They are most capable of degrading host complement proteins, cytokines, and host clotting factors mostly due to their serine centre or metallotype. Because of its potential usage in food, pharmaceutical, and other industrial domains, this category of enzymes has been extensively investigated. Specifically, serine proteases are a group of enzymes that can be consumed orally and are stable in our gastrointestinal tract. Conclusion: In this review, we discussed the role of different serine proteases in amyloid aggregate inhibition and their potential application in treating amyloidosis.